Co-application of biochars and Piriformospora indica improved the quality of coastal saline soil and promoted the growth of forage - Wu, Qicong; Ning, Ke; Liu, Bingqian; Zheng, Xuejia; Li, Chen; Li, Xin; Zhou, Xiaohu; Li, Jiawang; Li, Jiajing; Zhang, Congzhi; Dong, Zhi (Frontiers in Plant Science, 2024)
Soil quality Soil quality is defined as the ability of soil to maintain the soil environment and the biosphere, and due to the limitation of salt and alkali stress, soil quality can be reduced, which in turn affects agricultural production. is restricted by the elevated levels of salt ions and reduces agricultural production. Saline-alkali soil amendments, such as bBiochar is widely used in saline-alkali land improvement because of its special pore structure and strong ion exchange ability, while P. indica is widely used in saline-alkali land improvement because it can symbiosis with plants and improve plant stress resistance.iochar and Piriformospora indica (P. indica) have been extensively utilized to alleviate salinity stress. However, the synergistic effect of combined biochar application and inoculation of P. indica on the quality of saline-alkali soil and plant development is uncertain.Uncertainty surrounds the combined benefits of applying biochar and inoculating with P. indica on the enhancement of saline-alkali soils and plant development. Hence saline-alkali soil was used as a substrate towe investigated the combined influences of biochar and P. indica on the soil physicochemical characteristics, as well as the growth and chlorophyll florescence of sorghumsudangrass hybrids (Sorghum bicolor × Sorghum sudane) in our study. The results indicated that the combination application of P. indica and biochar showed enhanced soil physicochemical characteristics. Aafter applying biochar and P. indica together, there was a considerable drop in soil pH, conductivity, Na + , and Cl -concentrations. Meanwhile, the contents of soil organic matter (SOM), available phosphorus (AP), and alkaline hydrolyzable nitrogen (AN) increased by 151.81%, 50.84% and 103.50%, respectively, when the Bamboo biochar was combined with 120 mL/pot P. indica.Eventually, sorghum-sudangrass hybrid biomass, transpiration rate, and chlorophyll content increased by 111.69%, 204.98% and 118.54%, respectively. According to our findings, using P. indica and biochar together can enhance soil qualitysoil qualities and plant growth, this innovative approach has the potential to enhance coastal saline soils, presenting a novel avenue for improvement.The results also provide insights into enhancing enhance the quality of saline-alkali soils and the role of microorganisms in nutrient cycling.